Wyzwania rodzicielskie w ponowoczesności - Bakiera, Lucyna (Człowiek i Społeczeństwo, 2024)
Contemporary parents in Western culture operate within the context of social processes such as globalization, consumerism, relativism, individualism, and mediatization. These processes are manifestations of postmodernity, which significantly weakens the influence of tradition on the life choices of adults. Engagement in clearly defined and institutionalized roles, including parental roles, does not align with the postmodern lifestyle. Postmodernity presents mothers and fathers with numerous tasks on their journey to realizing personal parenting projects. Modern motherhood and fatherhood roles show considerable diversity – ranging from maintaining traditional forms, to adopting egalitarian approaches, to entirely new and individualized methods of parenting. This article serves as an introduction to a series of original discussions addressing the current challenges faced by parents.